Analysis of Natural Gas Hydrates using Inert Gases - Smith, Callum Conway (Curtin University, 2017)
This research focuses on the analysis of natural gas hydrates with the use of inert gases. Phase equilibria for several natural gas and methane-containing gas mixtures are analysed and used in the understanding of the influence each non-methane component instils towards the thermodynamic conditions for hydrate equilibria. Correlations and new thermodynamic data, namely dissociation enthalpies, are presented. These values are also used to compare the stability of structure I to structure II hydrates and establish a composition range where a transition occurs.